Effects of resistance training and estrogen replacement on adipose tissue inflammation in ovariectomized rats - Rodrigues, Maria Fernanda Cury; Ferreira, Fabiano Candido; Silva-Magosso, Natália Santanielo; Barbosa, Marina Rodrigues; Souza, Markus Vinicius Campos; Domingos, Mateus Moraes; Canevazzi, Gustavo Henrique Rigo; Stotzer, Uliana Sbeguen; Peviani, Sabrina Messa; de Lira, Fábio Santos [UNESP]; de Araújo, Heloísa Sobreiro Selistre; de Andrade Perez, Sérgio Eduardo (Canadian Science Publishing, 2017)
Estrogen deficiency is directly related to central obesity and low-grade inflammation. Hormonal replacement and exercise training are both able to decrease fat accumulation and inflammation in postmenopausal women. However, the efficiency of resistance training (RT) and estrogen replacement (ER) in minimizing adiposity and inflammation in the visceral adipose tissue (VAT) of ovariectomized (OVX) rats has not yet been elucidated. In this study, Sprague–Dawley rats were divided into the following 6 groups: sham-operated sedentary (Sham-Sed), OVX-Sed, Sham-RT, OVX-RT, OVX-Sed-ER, and OVX-RT-ER groups. ER was performed by implanting silastic capsules containing 17β-estradiol. For RT, the animals were required to climb a 1.1-m vertical ladder with conical flasks containing weights attached to their tails for 12 weeks. Histological analyses were used to evaluate morphological changes. Gene expression levels were determined by quantitative real-time reverse transcriptase polymerase chain reaction, and protein concentrations were determined using Multiplex/Luminex assays. Ovariectomy increased the body mass (BM), adipocyte area, and inflammation in the VAT, the latter of which was indicated by reduced interleukin-10 (48%) and increased tumor necrosis factor (TNF)-α concentration (~3%). RT efficiently decreased BM, adipocyte area, and inflammation in the OVX groups. The combination of RT and ER decreased BM (19%) and the TNF-α concentration (18%) and increased the gene and protein expression levels of adiponectin (173% and 18%). These results indicate that RT and the combination of RT and ER are efficient strategies for reducing the BM and improving the inflammatory status of OVX rats.
Keywords: Adipose tissue; Cytokines; Estrogen; Inflammation; Rats; Resistance training